Brief Online Training Enhances Competitive Performance: Findings of the BBC Lab UK Psychological Skills Intervention Study - Lane, Andrew M.; Totterdell, Peter; MacDonald, Ian; Devonport, Tracey J.; Friesen, Andrew P.; Beedie, Christopher J.; Stanley, Damian; Nevill, Alan (Frontiers in Psychology, 2016)
In conjunction with BBC Lab UK, the present study developed 12 brief psychological skill interventions for online delivery. A protocol was designed that captured data via self-report measures, used video recordings to deliver interventions, involved a competitive concentration task against an individually matched computer opponent, and provided feedback on the effects of the interventions. Three psychological skills were used; imagery, self-talk, and if-then planning, with each skill directed to one of four different foci: outcome goal, process goal, instruction, or arousal-control. This resulted in 12 different intervention participant groups (randomly assigned) with a 13th group acting as a control. Participants (n = 44,742) completed a competitive task four times–practice, baseline, following an intervention, and again after repeating the intervention. Results revealed performance improved following practice with incremental effects for imagery-outcome, imagery-process, and self-talk over the control group, with the same interventions increasing the intensity of effort invested, and increasing arousal via pleasant emotions. Arousal-control interventions associated with pleasant emotions and low effort. Instructional interventions were not effective. Results offer support for the utility of online interventions in teaching psychological skills.